Pendampingan SMK Negeri 6 Kerinci dalam Mewujudkan Sekolah Ramah Anak (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2022)
The problem of violence in the world of education becomes a very important topic to be solved, so there needs to be concrete action from the world of education such as realizing a Child Friendly School. The purpose of this assistance is to provide assistance in SMK Negeri 6 Kerinci in realizing a Child Friendly School. This method of mentoring is carried out through workshops, lectures and questions held on January 22, 2022. The scope of this activity was carried out in SMK Negeri 6 Kerinci with respondents to the entire academic community of SMK Negeri 6 Kerinci. The results of this assistance show that the academic community of SMK Negeri 6 Kerinci has good education and a strong joint commitment in realizing Child-Friendly Schools to make SMK Negeri 6 Kerinci as a Child-Friendly School Role Model in Kerinci Regency